The aspects of investigation of microorganism antibiotic resistance at the present stage - Andreeva, I; Makedonsky, I; Stepansky, D; Tchemeris, O (Annals of Mechnikov's Institute, 2020)
Introduction. At the present stage for ensuring epidemic safety and prevention of nosocomial infections the complex of analytical study and managerial procedure to improve the epidemiological supervision over nosocomial infections through the introduction of infection control in health care practice are using. The microbiological monitoring is part of the infectious control and allows supervising circulation of microorganisms and their antimicrobial resistance by dynamic observation over structure and level of resistance to antibiotics that are used in the given particular hospital. Materials and methods. For the dynamic observation of the structure and the level of resistance of microorganisms to antimicrobial agents the computer software WHONET recommended by WHO has been used. With using WHONET in Dnepropetrovsk Children's Hospital № 3 the computer database has been created. In this database the information about each patient, hospital department, samples under test and the date of its excretion, the data about the detected microorganism and its sensitivity/resistance to antimicrobial agents have been stored. The examination and analysis of antibiotic resistance of microorganisms has been provided for 2010-2014 years, in total the data on 6168 isolates from 3876 patients have been analyzed. Results and discussion. By the total data the isolates belong to a wide spectrum of microorganisms (more than 40 different types). By means of the analysis of isolating of clinically significant microorganisms it has been established that one of the most frequent isolated were Escherichia coli (1-20 %), Klebsiella pneumoniae (4-18 %), Staphylococcus epidermidis (1-12 %), S. aureus (1-10 %), Enterobacter cloacae (2-9 %), Pseudomonas aeruginosa (1-8 %). Detection of other microorganisms was irregular and its frequency is varied from 0 % to 10 %. As a result of examining the sensitivity of microorganisms it has been shown that tested strains of bacteria were resistant to 72.7 % (on the average) of antibiotics used in testing. In particular, resistance to ampicillin, ceftriaxonum, ceftazidime and gentamycin was high and reached 100 %. After the placed ban on the usage of these medicines in dynamics, there was observed a tendency to development to ampicillin, ceftriaxonum, ceftazidime and gentamycin in circulating strains of microorganisms. Conclusion. Improving quality of medical aid is possible by implementation of strategy of controllable application of antibiotics based on the results of microbiological monitoring using analytical computer program WHONET in practice of health protection establishments.